2020
DOI: 10.34172/ajcmi.2020.27
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Potassium Hydroxide Wet Mount, Calcofluor White Staining and Culture for the Diagnosis of Keratomycosis

Abstract: Background: The incidence of keratomycosis has increased dramatically in recent years. Early diagnosis and treatment of keratomycosis are important in preventing further complications. Direct microscopic techniques are time-saving for diagnosing keratomycosis when compared to culture methods. This study was carried out to determine the sensitivities of potassium hydroxide (KOH) wet mount, Gram stain and Calcofluor white (CFW) stain plus KOH wet mount by taking culture as the gold standard. Methods: Corneal scr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…The most frequent predisposing factor related to infectious keratitis in the current research was corneal trauma, with 14 (46.6%) cases, followed by steroid use, with 6 (20%), and DM, with 3 (10%). This came in agreement with a study conducted by Harbiyeli et al [27], Alekhya et al [28], and Mahmoud et al [29]. On the other hand, other publications showed different results as a study conducted by Gorski et al [30] who found that among 155 patients with microbial keratitis, contact lens wear was (39%) followed by corneal trauma (8%).…”
Section: Discussionsupporting
confidence: 89%
“…The most frequent predisposing factor related to infectious keratitis in the current research was corneal trauma, with 14 (46.6%) cases, followed by steroid use, with 6 (20%), and DM, with 3 (10%). This came in agreement with a study conducted by Harbiyeli et al [27], Alekhya et al [28], and Mahmoud et al [29]. On the other hand, other publications showed different results as a study conducted by Gorski et al [30] who found that among 155 patients with microbial keratitis, contact lens wear was (39%) followed by corneal trauma (8%).…”
Section: Discussionsupporting
confidence: 89%
“…The samples were then mounted using a coverslip and imaged using a live cell imager. 35,36 2.5 Antiviral efficacy of CuI (WH) and CuI (H) particles 2.5.1 Culturing and maintenance of lambda phage (U). The bacteriophage lambda (ATCC 23724-B2) was received as a gift sample from Dr Manjula Reddy, CSIR-CCMB, Hyderabad, India.…”
Section: Materials Advances Papermentioning
confidence: 99%
“…The samples were then mounted using a coverslip and imaged using a live cell imager. 35,36 2.5 Antiviral efficacy of CuI (WH) and CuI (H) particles…”
Section: Materials Advances Papermentioning
confidence: 99%